John Fisher papers - Fisher, John, active 1777-1802.
Correspondence, memoranda, accounts, purchase and delivery orders, receipts, requisitions, invoices, and other financial and mercantile records relating primarily to Fisher's Revolutionary War service as assistant deputy quartermaster at Fishkill, N.Y., and to his mercantile activities in New York. Documents the distribution of food and supplies to the Continental Army in Connecticut, New Jersey, and New York. Also includes salary and clothing reports for employees at Fishkill Landing, 1780-1782; lists of shipping vessels employed in public service, 1780-1782; invoices of supplies used by sloops on the Hudson River, 1778-1780; and a monthly table of depreciation for the Continental dollar from September 1777 to March 1780.
Correspondents include William Betts, Joseph Bowne, Anthony Byvanck, John Campbell, Daniel Carthy, D. Hale, E. Haskell, Udney Hay, Robert Henry, John Keese, Richard King, James McMaster, Christopher Meng, Uriah Mitchell, Richard Norwood, John Palmer, Henry Peckwell, Timothy Pickering, Richard Platt, Leonard Smith, Andrew Taylor, George Trimble, and Timothy Whiting.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Military supply agent and merchant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Betts, William, -- active 1777-1782 -- Correspondence; Bowne, Joseph -- Correspondence; Byvanck, Anthony -- Correspondence; Campbell, John, -- active 1777-1782 -- Correspondence; Carthy, Daniel -- Correspondence; Hale, D., -- active 1777-1782 -- Correspondence; Haskell, E., -- active 1777-1782 -- Correspondence; Hay, Udney -- Correspondence; Henry, Robert, -- active 1777-1782 -- Correspondence; Keese, John -- Correspondence; King, Richard, -- active 1777-1782 -- Correspondence; McMasters, James -- Correspondence; Meng, Christopher -- Correspondence; Mitchell, Uriah -- Correspondence; Norwood, Richard -- Correspondence; Palmer, John, -- active 1777-1782 -- Correspondence; Peckwell, Henry -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Platt, Timothy -- Correspondence; Smith, Leonard, -- active 1777-1782 -- Correspondence; Taylor, Andrew, -- active 1777-1782 -- Correspondence; Trimble, George, -- active 1777-1782 -- Correspondence; Whiting, Timothy -- Correspondence; United States. -- Continental Army -- Supplies and stores; Merchants -- New York (State) -- New York; Money -- United States; Ships -- United States; Sloops -- Hudson River (N.Y. and N.J.); Connecticut -- History -- Revolution, 1775-1783.; Fishkill (N.Y.) -- History; New Jersey -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Merchants